2021
DOI: 10.1158/1078-0432.ccr-21-3151
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free HPV DNA Provides an Accurate and Rapid Diagnosis of HPV-Associated Head and Neck Cancer

Abstract: Purpose: HPV-associated head and neck squamous cell carcinoma (HPV+HNSCC) is the most common HPV-associated malignancy in the United States and continues to increase in incidence. Current diagnostic approaches for HPV+HNSCC rely on tissue biopsy followed by histomorphologic assessment and detection of HPV indirectly by p16 IHC. Such approaches are invasive and have variable sensitivity. Experimental Design: We conducted a pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
68
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 63 publications
(82 citation statements)
references
References 42 publications
0
68
0
1
Order By: Relevance
“…We found that POD 1 ctHPVDNA levels are associated with the risk of residual disease. These findings are the first to demonstrate the potential utility of ctHPVDNA as a tool for personalized treatment decision‐making in patients with HPV+OPSCC undergoing surgery and add to a growing body of literature which support ctHPVDNA use as a diagnostic test and a biomarker of treatment response and recurrence after CRT 20,21,26 …”
Section: Discussionmentioning
confidence: 66%
See 4 more Smart Citations
“…We found that POD 1 ctHPVDNA levels are associated with the risk of residual disease. These findings are the first to demonstrate the potential utility of ctHPVDNA as a tool for personalized treatment decision‐making in patients with HPV+OPSCC undergoing surgery and add to a growing body of literature which support ctHPVDNA use as a diagnostic test and a biomarker of treatment response and recurrence after CRT 20,21,26 …”
Section: Discussionmentioning
confidence: 66%
“…Five ddPCR assays were developed and optimized to detect conserved regions of E7 from HPV 16, 18, 33, 35, and 45 26 . Probes were confirmed to have no cross‐genotype reactivity, to be linear ( R 2 > 0.96 for all genotypes), and to have limits of detection ≤0.1% fractional abundance.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations